Treatment of Noninfectious Retinal Vasculitis Using Subcutaneous Repository Corticotropin Injection - Anesi, Stephen D. (J Ophthalmic Vis Res, 2021)
PURPOSE: To show whether subcutaneous repository corticotropin injection (RCI, Acthar® Gel, a repository corticotropin injection, can be an effective potential therapeutic agent for noninfectious retinal vasculitis. METHODS: Patients with active retinal vasculitis were followed with serial ultra-wide-field fluorescein angiograms and treated with 80 units of subcutaneous repository corticotropin injection twice weekly. RESULTS: Primary outcome of [Formula: see text] 50% improvement in response level (RL) for retinal vasculitis and percent improvement in retinal vasculitis severity scoring (RVSS) by more than one quartile ([Formula: see text] 25%) at week 12 was met in 15 and 16 of the 30 total eyes, respectively, including 1 eye with severe retinal vasculitis in each group. Complete resolution of retinal vasculitis was seen in seven eyes with a mean time of 17.1 weeks. Intraocular pressure elevation requiring therapy and cataract progression were noted in two and three eyes, respectively. One patient stopped medication due to side effects (injection site reaction). CONCLUSION: Repository corticotropin injection was well-tolerated overall. Repository corticotropin injection may be an effective therapeutic agent in the treatment of noninfectious retinal vasculitis.